Percutaneous microwave ablation for HCV-related hepatocellular carcinoma: Efficacy, safety, and survival - Darweesh, Samar K.; Gad, Amal A. (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Hepatocellular carcinoma (HCC) has a poor prognosis if managed late. Percutaneous microwave ablation (MWA) emerged as one of the top therapeutic decisions for non-surgical patients. The aim of the present study aim was to evaluate the efficacy, side effects, and survival after MWA of hepatitis C virus (HCV)-related HCC tumors with spectrum sizes up to 5 cm. Materials and Methods: Fifty-nine patients with early HCC were treated in the Hepatology Department using percutaneous MWA. Patients were assessed for side effects and efficacy that includes the rate of complete ablation, primary or de novo recurrence, and survival. Results: Complete ablation was achieved in 57 (96.6%) patients treated by MWA, with a minor complication rate of 3.3% (n=2) including liver abscess formation and abdominal skin burn. The ablation rates in lesions 3 cm), and 2 (3.3%) had malignant portal vein thrombosis. The survival rates were 95.4% and 69% at 1 and 2 years, respectively. Conclusion: Percutaneous MWA had achieved a safe and effective treatment with good overall survival in patients with HCV-related HCC. Cite this article as: Darweesh SK, Gad AA. Percutaneous microwave ablation for HCV-related hepatocellular carcinoma: Efficacy, safety, and survival. Turk J Gastroenterol 2019; 30(5): 445-53.